2015
DOI: 10.1039/c5cp00156k
|View full text |Cite
|
Sign up to set email alerts
|

Phase stability, chemical bonding and mechanical properties of titanium nitrides: a first-principles study

Abstract: We have performed first-principles evolutionary searches for stable Ti-N compounds and have found, in addition to the well-known rock-salt TiN, new ground states Ti3N2, Ti4N3, Ti6N5 at atmospheric pressure, and Ti2N and TiN2 at higher pressures. The latter nitrogen-rich structure contains encapsulated N2 dumbbells with a N-N distance of 1.348 Å at 60 GPa. TiN2 is predicted to be mechanically stable and quenchable. Our calculations on the mechanical properties (bulk modulus, shear modulus, Young's modulus, Pois… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
112
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(127 citation statements)
references
References 56 publications
15
112
0
Order By: Relevance
“…Ti 3 N 2 is orthorhombic structure which belongs to space group of Immm. By geometry optimization, the calculated lattice parameters for c-BN, TiN, Ti 2 N and Ti 3 N 2 at 0 GPa and 50 GPa are presented in Table 1 [25,[32][33][34][35], which show that the present optimization and calculations are reliable.…”
Section: Structural Propertiesmentioning
confidence: 78%
See 1 more Smart Citation
“…Ti 3 N 2 is orthorhombic structure which belongs to space group of Immm. By geometry optimization, the calculated lattice parameters for c-BN, TiN, Ti 2 N and Ti 3 N 2 at 0 GPa and 50 GPa are presented in Table 1 [25,[32][33][34][35], which show that the present optimization and calculations are reliable.…”
Section: Structural Propertiesmentioning
confidence: 78%
“…However, most of their studies focus on the stoichiometric rock-salt TiN, and there are a few studies of non-stoichiometric titanium nitrides. Yu et al [25] made first-principles evolutionary searches for stable Ti-N compound and found, in addition to the well-known rock-salt TiN, new ground states Ti 3 N 2 , Ti 4 N 3 , Ti 6 N 5 at atmospheric pressure, and Ti 2 N and TiN 2 at higher pressure. They also gave the mechanical properties of the Ti-N compounds at 0 GPa.…”
Section: Introductionmentioning
confidence: 98%
“…Very recently, titanium pernitride, TiN 2 , was investigated theoretically, 89,90 and was then synthesized under high-pressure synthesis at 73 GPa, with a bulk modulus in the range 360−385 GPa. 70 We calculate the Δμ N 2 for TiN 2 to be +1.18 eV/N, much higher than the precious metal pernitrides.…”
Section: Chemistry Of Materialsmentioning
confidence: 99%
“…Transition-metal (TM) nitride refractory ceramics possess outstanding physical and mechanical properties, including extreme hardness [1][2][3], high toughness [4][5][6], thermal stability [7,8], chemical inertness [9,10], and good electrical conductivity [2,11], which renders them important for a large variety of applications ranging from wear-resistant protective coatings on tools employed in industrial machining [12,13] to diffusion barrier in electronic devices [14,15].…”
Section: Introductionmentioning
confidence: 99%